Establishment of patient-derived 3D in vitro models of sarcomas: literature review and guidelines on behalf of the FORTRESS working group - De Cock, Lore; Palubeckaitė, Ieva; Bersani, Francesca; Faehling, Tobias; Pasquali, Sandro; Umbaugh, Sam; Meister, Michael Torsten; Danks, Molly R.; Manasterski, Piotr; Miallot, Richard; Krumbholz, Manuela; Roohani, Siyer; et al. (Neoplasia, 2025)
Sarcomas are a large family of rare and heterogeneous mesenchymal tumors, which respond poorly to available systemic treatments. Translation of preclinical findings into clinical applications has been slow, limiting improvements in patients’ outcomes and ultimately highlighting the need for a better understanding of sarcoma biology to develop more effective, subtype-specific therapies. To this end, reliable preclinical models are crucial, but the development of 3D in vitro sarcoma models has been lagging behind that of epithelial cancers. This is primarily due to the rarity and heterogeneity of sarcomas, and lack of widespread knowledge regarding the optimal growth conditions of these in vitro models. In this review, we provide an overview of currently available sarcoma tumoroid models, together with guidelines and suggestions for model development and characterization, on behalf of the FORTRESS (Forum For Translational Research in Sarcomas) international research working group on 3D sarcoma models.